Implementasi Sistem Keuangan Syariah dalam Pengembangan Unit Usaha BUMDes: Upaya Meningkatkan Ekonomi Lokal Desa Mertoyudan Jawa Tengah - Achmad Rabbani (Athallah Publishing Globalndo, 2025)
This study aims to analyze the implementation of the sharia financial system in the development of Village-Owned Enterprises (BUMDes) as a strategy to improve the local economy in Mertoyudan Village, Magelang Regency, Central Java. In facing the challenges of village development, BUMDes plays a strategic role as a driving force for the community's economy. The sharia approach in the financial system is believed to be able to encourage the creation of ethical, fair, and sustainable businesses. This study uses a qualitative method with data collection techniques through in-depth interviews, field observations, and documentation studies. The results of the study indicate that the implementation of sharia financial principles, such as mudharabah and musyarakah contracts, can strengthen the capital of BUMDes business units and increase community participation and trust. Although there are challenges in terms of community understanding and management capacity, collaboration between village officials, BUMDes managers, and religious leaders is the key to success. In conclusion, the sharia financial system has great potential in supporting inclusive and value-based village economic development.